SKRINING FITOKIMIA DAN UJI TOKSISITAS AKUT EKSTRAK DAUN BEREMBANG (Sonneratia caseolaris) SEBAGAI ANTI HIPERTENSI - HERIKA, HERIKA (Department of Biology Education, Faculty of Teacher Training and Education, Samudra University, 2018)
Berembang (Sonneratia caseolaris) is a plant that lives on the banks of river mouths, especially in areas with low salinity mixed with fresh water found in the mangrove ecosystem. The fruit’s berembang (Sonneratia caseolaris) has been used as a traditional medicine, analgesic, anti-inflammatory and antibacterial properties. Fruit’s berembang (Sonneratia caseolaris) contains flavonoid compounds. Flavonoids have been known to have antihypertensive effects. But the research that has been done is only limited to the developing fruit and has not been studied in developing leaves. The aim of this study was to determine the content of chemical compounds found in the developing leaves (Sonneratia caseolaris) and toxicity test of developing leaf extract (Sonneratia caseolaris). The results of phytochemical screening showed that the fluffy leaves (Sonneratia caseolaris) contained flavonoid and tannin compounds. The results of acute toxicity tests at the highest dose of 400 mg/kg BW were not found to be dead mice. So that the fluffy leaves are categorized as not toxic and safe for consumption. The results of this study will then be used as a basis for testing the leaf extract (Sonneratia caseolaris) as an antihypertensive. It is expected to help the community in the treatment of hypertension.